Synergistic Effects of Electron-beam Irradiation and Leek Extract on the Quality of Pork Jerky during Ambient Storage - Kim, Hyun-Joo (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
To investigate the synergistic effect(s) of electron-beam (EB) irradiation and leek (Allium tuberosum Rottler) extract on the quality of pork jerky during ambient storage, we irradiated prepared pork jerky samples (control and samples with 0.5% and 1.0% leek extract) with EB technology at doses of 0, 1, 2, and 4 kGy, stored them for 2 months at 25°C, and analyzed them. Water activity was 0.73 to 0.77 in non-irradiated samples, and no significant difference in the water activity was observed between the samples treated with leek and the control. The total aerobic bacterial count was significantly decreased with an increase in the irradiation dose and leek extract addition when compared to that of the control (4.54±0.05 log CFU/g). Further, the Hunter color values (L*, a*, and b*) were found to be significantly decreased following leek extract addition and EB irradiation. However, the color values, especially the a* value of the irradiated samples significantly increased during storage. Notably, increasing the EB irradiation dose enhanced the peroxide value. Sensory evaluation revealed that irradiation decreased flavor and overall acceptability. Our findings suggest the use of EB irradiation in combination with leek extract to improve the microbiological safety of pork jerky. However, in order to meet market requirements, novel methods to enhance the sensory quality of pork jerky are warranted.